The Expressive Utterances Found in the Song Love You Like A Love Song by Selena Gomez - Suryaningsih*, Rah Tri; Musyarofah, Lailatul; Putranto, Henry Rio (Riwayat: Educational Journal of History and Humanities, 2024)
The study discussed the analysis of expressive utterences found in the lyrics of the song "Love You Like a Love Song" by Selena Gomez and became one of the hits in the music world. The purpose of this study is to examine whether there is a match between song lyrics and the expressive expressions conveyed. Song has an important role as an expressive medium because it is able to convey messages and emotions effectively. The research used descriptive qualitative, namely by analyzing the text and contextual approach to understand the meaning of song lyrics and their effect on listeners. The results of the analysis of expressive utterences in the lyrics show their suitability with the theme of the song and the communicative purpose of conveyed true love. The conclusion of the study is to provide an overview of how the lyrics of the song describe feelings of love expressively through the used of symbolic words and melodies that touch the heart.